Urbanization and education as factors of the age specificity of reproductive behaviour - Belov, Andrei А. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to study of impact of urbanization and education on the fertility rate in the Republic of Belarus. The study was conducted on the basis of the population census. Cumulative fertility rates are considered in the hypothetical generation of women, depending on educational levels and the types of settlement. A quantitative estimation of effects on the fertility rate of each of the factors under consideration is carried out. It is concluded that both factors exert the greatest influence on the level of fertility through the increase in the age at which the reproductive attitudes begin to be realized.
Keywords: reproductive behaviour; urbanization; educational level; cumulative fertility rate; hypothetical generation